1999
DOI: 10.1046/j.1365-3083.1999.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Analysis of Recombinant Salmon Parvalbumin, the Major Allergen in Atlantic Salmon (Salmo salar)

Abstract: The parvalbumin from white muscle of Atlantic salmon was previously found to be a major allergen, and designated Sal s1. Two distinct cDNAs, 14.1 and 24.1, which comprise the entire parvalbumin‐encoding regions, were cloned, revealing transcripts from two different parvalbumin genes. In the present study, the protein‐coding regions of these cDNAs were subcloned into an Escherichia coli expression vector (pET‐19b). Both proteins were expressed and the generated target proteins were localized in both soluble and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The first and best-identified parvalbumin allergen is Gad c 1 from codfish Gadus callarias which has high cross-reactivity between different fish species [6,17]. In subsequent molecular studies, parvalbumin has been identified as major allergen in multiple species of fish, such as salmon [18], Atlantic cod [19], carp [20,21], mackerel [22,23], Alaska pollack [24], blunt snout bream [25] and red stingray [26]. In addition to parvalbumin, within the last several years some studies have identified higher-MW fish allergens, including aldehyde phosphate dehydrogenase [27], collagen [28,29,30], transferrin [31], enolase and creatine kinase [25].…”
Section: Introductionmentioning
confidence: 99%
“…The first and best-identified parvalbumin allergen is Gad c 1 from codfish Gadus callarias which has high cross-reactivity between different fish species [6,17]. In subsequent molecular studies, parvalbumin has been identified as major allergen in multiple species of fish, such as salmon [18], Atlantic cod [19], carp [20,21], mackerel [22,23], Alaska pollack [24], blunt snout bream [25] and red stingray [26]. In addition to parvalbumin, within the last several years some studies have identified higher-MW fish allergens, including aldehyde phosphate dehydrogenase [27], collagen [28,29,30], transferrin [31], enolase and creatine kinase [25].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The first identified fish allergen is parvalbumin of cod Gadus callarias , a calcium-binding sarcoplasmic protein with a molecular mass of approximately 12 kDa. 6,7 Subsequent immunoblotting studies 2,8-10 and molecular studies [11][12][13][14][15][16][17][18] have established that parvalbumin represents the major and cross-reactive allergen in common with various species of fish, although minor allergens, such as collagen [19][20][21] and aldehyde phosphate dehydrogenase, 22 have been detected simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is generally laborious and time-consuming to purify allergens from biological samples, recent molecular genetic techniques enable us to easily obtain large amounts of recombinant allergens at need. Along this line, the cDNA coding for allergens (parvalbumins) of Atlantic salmon Salmo salar , 15 carp Cyprinus carpio 16 and Atlantic cod Gadus morhua 17 have been cloned and expressed in Escherichia coli and the resulting recombinant allergens evaluated for IgE-binding capacity. However, these previous studies have been all performed in Europe and, hence, no recombinant fish parvalbumins are available in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…8 In this work we sought factories with fillet processing as well as slaughteries, to include a worker group primarily exposed to fish muscle, bearing the main antigen parvalbumin. 14 Municipal workers formed the control group without exposure of interest. We aimed to compare respiratory status in salmon-processing workers and controls by estimating prevalence of general and work-related respiratory symptoms, variables of lung function and blood tests, and concentration of nitric oxide in exhaled air.…”
mentioning
confidence: 99%